2006
DOI: 10.1111/j.1600-0684.2006.00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Foamy virus infection in primates

Abstract: Foamy viruses (FV), the oldest known genus of Retroviridae, are unique among the retroviruses in having no disease association. It is not known why FV are non-pathogenic while infection by their closest relatives can be deadly. This may be related to the estimated 60 million years of coevolution of FV and their primate hosts. We review the current state of knowledge of FV infection, including information about the sites of viral replication and host immune responses, and discuss the role these may play in esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
77
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 95 publications
9
77
0
3
Order By: Relevance
“…They are highly prevalent in several animal species, particularly in nonhuman primates (NHPs), in which they establish persistent infections (19), with the documented level of infection being 75 to 100% of captive adult NHPs. Most of the captive animals examined have been macaques and baboons (3,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They are highly prevalent in several animal species, particularly in nonhuman primates (NHPs), in which they establish persistent infections (19), with the documented level of infection being 75 to 100% of captive adult NHPs. Most of the captive animals examined have been macaques and baboons (3,7).…”
mentioning
confidence: 99%
“…The oral mucosa has been shown to be the main site of SFV replication in vivo, and saliva appears to be the principal reservoir of SFV (20). In NHPs, SFV is presumed to be transmitted mainly through severe bites, thus involving contact between infected saliva and blood (3,7,19). Other factors could play an important role in SFV transmission: for example, Leendertz et al demonstrated that SFV can be transmitted to chimpanzees after the consumption of smaller NHPs, such as colobus monkeys (16).…”
mentioning
confidence: 99%
“…They are highly prevalent in nonhuman primates, with at least 16 different simian viral subtypes (6,19,49,51,52,69). FV are particularly well adapted to their natural hosts.…”
mentioning
confidence: 99%
“…They cause a persistent infection, but there are no known pathologies in natural or human hosts. 50,51 It has been suggested that SFVs have coevolved with their Old World primate hosts for over 30 million years, marking them as the oldest known RNA viruses in vertebrates. 52 A3 proteins have been implicated in restriction of FVs, and the FV accessory protein Bet has been found to counteract A3 restriction mechanisms analogously to HIV-1 Vif.…”
Section: Discussionmentioning
confidence: 99%